EFEKTIVITAS METODE PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR SISWA PADA BIMBINGAN TEKNIK INFORMATIKA DAN KOMPUTER (TIK) KELAS XII MIPA DI SMAN 1 PARIAMAN - Rhadiatur Rahmah; Supriadi Supriadi; Hari Antoni Musril; Riri Okra (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of the author raised this point because the learning and teaching process in general still uses conventional methods. The results achieved are less than optimal and student activity is less visible. This method causes students to tend to be passive and only listen. So, one of the efforts that teachers can make so that students are able to participate in learning is by using the Group Investigation (GI) type of cooperative learning model. The method used in this research is to use a quantitative method of experimental type with a pre-experimental research design in the form of one group pretest-posttest design. The population in this study were all students of class XII MIPA at SMA N 1 Pariaman. Sampling used a non-probability sampling technique, namely purposive sampling where class XII MIPA1 was the experimental class and class XII was MIPA as the control class. The data on ICT learning research results were obtained from the final test. The results of the study, based on data analysis, it was known that the final test of ICT learning outcomes was calculated using a t-test with the help of the SPSS version 2.5 application. From these results it is clear that the calculation obtained that H0 is rejected because tcount = -10,524 is greater than ttable = 0.339 and P-value = 0.0000. From these results it can be said that,